2023
DOI: 10.1039/d3sc02662k
|View full text |Cite
|
Sign up to set email alerts
|

How orange carotenoid protein controls the excited state dynamics of canthaxanthin

Amanda Arcidiacono,
Davide Accomasso,
Lorenzo Cupellini
et al.

Abstract: Orange Carotenoid Protein (OCP) is a ketocarotenoid-binding protein essential for photoprotec- tion in cyanobacteria. The main steps of the photoactivated conversion which converts OCP from its resting state to the...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
2
5
0
Order By: Relevance
“…The QM adiabatic electronic energies of carotenoids were computed using a SE configuration interaction (CI) approach, which proved to be effective in the description of their low-lying excited states. , This method performs a CI calculation within an active space. The targets E normalb normalr normali normalg normalh normalt and E normald normala normalr normalk used to train the ML models were obtained by performing our diabatization strategy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The QM adiabatic electronic energies of carotenoids were computed using a SE configuration interaction (CI) approach, which proved to be effective in the description of their low-lying excited states. , This method performs a CI calculation within an active space. The targets E normalb normalr normali normalg normalh normalt and E normald normala normalr normalk used to train the ML models were obtained by performing our diabatization strategy.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, for our purposes, it proved to be more efficient than other, more general, diabatization strategies. For example, a diabatization based on the maximization of the overlap matrix with reference states was used for carotenoids in various previous works by some of us, but it is less efficient when applied to geometries that are very different from the one used as a reference . Another issue generally regarding property-unblending strategies, like the one employed here, is that the sign of the diabatic couplings (off-diagonal elements of D ) is arbitrary and can be inconsistent from geometry to geometry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better characterize the nature of the electronic states during the ultrafast dynamics, we employ a diabatic representation in the same way as reported in our previous works. [24,25] More specifically, the diabatic states are defined so that they maximally resemble the lowest adiabatic singlet states of lutein (S 0 -S 3 ) at its S 0 minimum geometry, and are indicated using their (pseudo)symmetry, i.e., 1Ag − , 2Ag − , 1B + u , and 1B − u (more details are provided in Section 2.2). Figure 3b displays the diabatic state population dynamics for L1-Lut (left panel) and L2-Lut (right panel).…”
Section: Ultrafast Decay Pathway Of the S2 State Of Lutein: L1 Vs L2mentioning
confidence: 99%
“…[24] Furthermore, some of us have recently extended the application of the same methodology to the excited state dynamics of another carotenoid (canthaxanthin) in the Orange Carotenoid Protein (OCP). [25] Strikingly, these investigations suggested that the dark state S x is equally involved in the ultrafast decay pathway of the S 2 state of the two different carotenoids.…”
Section: Introductionmentioning
confidence: 98%